1992
DOI: 10.1039/c39920000310
|View full text |Cite
|
Sign up to set email alerts
|

Acid-catalysed C–H activation of ethene and linking of alkynes at a diruthenium centre

Abstract: The Ru=Ru double-bonded p-alkyne complexes [ R u ~( ~-C O ) ( ~-R C ~R ) ( ~-C ~H ~) ~] react slowly or not at all with ethene and alkynes even under forcing conditions, but in the presence of acid C-H activation of ethene and alkyne-linking occur rapidly at room temperature to give di-p-vinyl complexes [ R u ~( C O ) ( ~-C R = C H R ) ( ~-C H = C H ~) ( ~-C ~H ~) ~] and metallacyclopentadiene complexes [Ru2(CO)( p-C4R4)(q-C5H5)2] respectively; the acid catalysis is shown to proceed via the formation of a Ru-R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 5 publications
2
5
0
Order By: Relevance
“…The Ru--Ru distance compares well with those found in a variety of related species, e.g. (Cp) (Brady, Dyke, Garner, Guerchais, Knox, Maher, Nicholls & Orpen, 1992). Both the {Ru2(/z-CO)2} core and the cyclopentadienyl ring are planar within experimental error and the dihedral angle between these weighted least-squares planes is 130.5 (2) ° .…”
Section: Commentsupporting
confidence: 57%
“…The Ru--Ru distance compares well with those found in a variety of related species, e.g. (Cp) (Brady, Dyke, Garner, Guerchais, Knox, Maher, Nicholls & Orpen, 1992). Both the {Ru2(/z-CO)2} core and the cyclopentadienyl ring are planar within experimental error and the dihedral angle between these weighted least-squares planes is 130.5 (2) ° .…”
Section: Commentsupporting
confidence: 57%
“…1.5 h. Removal of solvent under reduced pressure then chromatography produced a purple band, eluted with dichloromethane-hexane (3 : 7), which yielded 0.34 g (80%) of the purple microcrystalline solid [Ru3(C0),(p-CO)(p3-CO)(p3-C2Ph,)(q-C5H5)2] 4 (Found : C,46.35;H,2.65%;A4 754. C29H200,Ru,requires C,46.15;H,2.65%; M 754); v(C0) (hexane) at 2053s, 1991m, 1987m, 1809m and 1742 cm-'. NMR (CDCl,): 'H, major isomer 4a 10 H,2 Ph) CPh),151.0,149.3,128.6,127.7,127.1,124.9 (2 Ph),94.8 (s,C,HJ and 89.2 (s,C5H5).…”
Section: Synthesis-[ru2fe(co)(p-co)(p3-co)(p3-c2ph2)(q-c-mentioning
confidence: 99%
“…Knox and co-workers reported the unexpected stability of the μ-alkyne-μ-carbonyl complex [(CpRu) 2 (μ-η 2 :η 2 -RCCR')(μ-CO)], despite its unsaturated electron configuration. [42] However, they found that the μ-η 2 :η 2 -alkyne complex became reactive in the presence of a catalytic amount of acid. In the presence of tetrafluoroboric acid, [(CpRu) 2 (μ-η 2 :η 2 -CF 3 CCCF 3 )(μ-CO)] reacted with ethylene at 25°C to yield a bis(μ-vinyl) complex, [(CpRu) 2 {μ-η 2 -C(CF 3 ) = C(CF 3 )H}(μ-η 2 -CH=CH 2 )(CO)], via CÀ H bond cleavage of ethylene.…”
Section: Resultsmentioning
confidence: 99%
“…Knox and co‐workers reported the unexpected stability of the μ‐alkyne‐μ‐carbonyl complex [(CpRu) 2 (μ‐η 2 :η 2 ‐RCCR′)(μ‐CO)], despite its unsaturated electron configuration [42] . However, they found that the μ‐η 2 :η 2 ‐alkyne complex became reactive in the presence of a catalytic amount of acid.…”
Section: Resultsmentioning
confidence: 99%